(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the features of finance in a market economy, which are associated with the collection, distribution, use of money in society, communication, the amount of relations, the role and significance of the requirements of commodity-money relations in the market Saving.